The plastid genome of Najas flexilis: adaptation to submersed environments is accompanied by the complete loss of the NDH complex in an aquatic angiosperm. - Elena L Peredo; Ursula M King; Donald H Les (PLoS ONE, 2013)
The re-colonization of aquatic habitats by angiosperms has presented a difficult challenge to plants whose long evolutionary history primarily reflects adaptations to terrestrial conditions. Many aquatics must complete vital stages of their life cycle on the water surface by means of floating or emergent leaves and flowers. Only a few species, mainly within the order Alismatales, are able to complete all aspects of their life cycle including pollination, entirely underwater. Water-pollinated Alismatales include seagrasses and water nymphs (Najas), the latter being the only freshwater genus in the family Hydrocharitaceae with subsurface water-pollination. We have determined the complete nucleotide sequence of the plastid genome of Najas flexilis. The plastid genome of N. flexilis is a circular AT-rich DNA molecule of 156 kb, which displays a quadripartite structure with two inverted repeats (IR) separating the large single copy (LSC) from the small single copy (SSC) regions. In N. flexilis, as in other Alismatales, the rps19 and trnH genes are localized in the LSC region instead of within the IR regions as in other monocots. However, the N. flexilis plastid genome presents some anomalous modifications. The size of the SSC region is only one third of that reported for closely related species. The number of genes in the plastid is considerably less. Both features are due to loss of the eleven ndh genes in the Najas flexilis plastid. In angiosperms, the absence of ndh genes has been related mainly to the loss of photosynthetic function in parasitic plants. The ndh genes encode the NAD(P)H dehydrogenase complex, believed essential in terrestrial environments, where it increases photosynthetic efficiency in variable light intensities. The modified structure of the N. flexilis plastid genome suggests that adaptation to submersed environments, where light is scarce, has involved the loss of the NDH complex in at least some photosynthetic angiosperms.